âMata Ketigaâ: SÃ¨ LaÃ¨n, Sang Pembebas Sistem Pendidikan Tinggi Akuntansi - Triyuwono, Iwan (Jurnal Akuntansi Multiparadigma, 2010)
The objectives of the study are to criticize the existing accounting education especially in Indonesian universities and to give an alternative idea for a better one. It is done as there is a strong indication that accounting education is driven by intellectual intelligence, market, and other artificial interests.Â  Through a deconstruction approach and critical analysis, the study suggests the internalization of âMata Ketigaâ (the Third Eye) in accounting curriculum.Â  Mata Ketiga, that refers to spiritual intelligence, is âthe Otherâ that is consciously entered to the singularity ofÂ  intellectual intelligence of modern curriculum. Under the internalization of Mata Ketiga, accounting education can be emancipated from the domination of intellectual intelligence, market, and other artificial interests.Â  By doing so, the education may guide an accounting student to find his/her âreal selfâ without neglecting contemporary accounting competence.